Deep learning-based tumor microenvironment analysis in colon adenocarcinoma histopathological whole-slide images. (June 2021) - Jiao, Yiping; Li, Junhong; Qian, Chenqi; Fei, Shumin
Highlights: Use the convolutional neural network to process colon adenocarcinoma whole-slide images. Automatic tumor microenvironment analysis based on whole-slide segmentation. Stroma, necrosis, and lymphocytes are found to be correlated with clinical outcomes. Abstract: Background and Objective: : Colon cancer is a fatal disease, and a comprehensive understanding of the tumor microenvironment (TME) could lead to better risk stratification, prognosis prediction, and therapy management. In this paper, we focused on the automatic evaluation of TME in giga-pixel digital histopathology whole-slide images. Methods: : A convolutional neural network is used to recognize nine different content presented in colon cancer whole-slide images. Several implementation details, including the foreground filtering and stain normalization are discussed. Based on the whole-slide segmentation, several TME descriptors are quantified and correlated with the clinical outcome by Kaplan-Meier analysis and Cox regression. Specifically, the stroma, tumor, necrosis, and lymphocyte components are discussed. Results: : We validated the method on colon adenocarcinoma cases from The Cancer Genome Atlas project. The result shows that the stroma is an independent predictor of progression-free interval (PFI) after corrected by age and pathological stage, with a hazard ratio of 1.665 (95%CI: 1.110 2.495, p = 0.014). High-level necrosis component and lymphocytes component tend to be correlated with poor PFI, with a hazard ratio of 1.552 (95%CI: 0.943 2.554, p = 0.084) and 1.512 (95%CI: 0.979 2.336, p = 0.062), respectively. Conclusions: : The result reveals the complex role of the tumor microenvironment in colon adenocarcinoma, and the quantified descriptors are potential predictors of disease progression. The method could be considered for risk stratification and targeted therapy and extend to other types of cancer, leading to a better understanding of the tumor microenvironment.